La actitud emprendedora durante la vida académica de los estudiantes universitarios - Espíritu Olmos, Roberto; Sastre Castillo, Miguel Ángel (Cuadernos de Estudios Empresariales, 2007)
The objective of the present research consists of analyzing if the Universities, as organisms that might act as incubators of business ideas, really are fulfilling this role and are stimulating the entrepreneurship attitude among their students, through the structure of its studies and the specific measures that they undertake. The raised hypotheses over of the higher training in their studies, generic and specific, they are confirmed using a sample of 668 students of a university of Madrid. The obtained conclusions invite to the reflection, while the students of more recent incorporation to the University present rates of entrepreneurship attitude higher to those of more veteran colleagues.